2022
DOI: 10.1039/d2cc03928a
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective synthesis of 3-trifluoromethyl 1,2,4-triazoles via photocycloaddition of sydnone with CF3CN

Abstract: A general and regioselective synthesis of 3-trifluoromethyl 1,2,4-triazoles has been achieved through photocycloaddition of sydnone with trifluoroacetonitrile. This method employed trifluoroacetaldehyde O-(aryl)oxime as CF3CN precusor and tolerated various functional groups...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…With this hypothesis in hand, we first examined the proposed condensation by using benzene-1,2-diamine ( 2a ) with a trifluoroacetonitrile precursor 1 , 31 and optimization of the reaction was carried out with a variety of bases, and solvents (Table 1). The reaction of 2a with 1 (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this hypothesis in hand, we first examined the proposed condensation by using benzene-1,2-diamine ( 2a ) with a trifluoroacetonitrile precursor 1 , 31 and optimization of the reaction was carried out with a variety of bases, and solvents (Table 1). The reaction of 2a with 1 (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…29 Also, we have recently demonstrated new efficient protocols for assembling a range of novel five-membered nitrogen-containing heterocycles using in situ generated trifluoroacetonitrile from 2,2,2-trifluoroacetaldehyde O-(aryl)oxime. [30][31][32][33] On the basis of these previous studies, especially on the synthesis of benzothiazoles and their structural analogues by the condensation of 2-aminothiophenol and nitriles, [34][35][36] and our continued interest in trifluoromethylated heterocycle synthesis, [37][38][39][40][41] we further became interested in designing efficient methodologies for the synthesis of 2-trifluoromethyl benzimidazoles and benzothiazoles via condensation of diamines or amino(thio)phenols with CF 3 CN (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…27 The utility of pyridinium 1,4-zwitterionic thiolates in synthesis has been recently developed by Zhai's group in a variety of cycloaddition reactions. 28–30 On the basis of our recent studies on the synthesis of trifluoromethylated heterocycles using trifluoroacetonitrile generated from 2,2,2-trifluoroacetaldehyde O -(aryl)oxime, 31–34 we predicted a similar mechanistic pathway for the reaction of pyridinium 1,4-zwitterionic thiolates with CF 3 CN, to generate 2-trifluoromethyl thiazoles (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the procedures to synthesize 1,2,4‐triazoles and derivatives under photoredox‐mediated conditions are rather limited. The examples include organophotocatalytic or photocatalyst‐free multicomponent annulations or dipolar cycloadditions to obtain 1,2,4‐triazoles functionalized regioselectively with groups such as diamine, [14a] trifluoromethyl, [14b] carboxylate ester etc [14c] . The research group of Li and Tang reported visible light photoredox synthesis of 1,2,4‐triazolines and triazoles through a redox‐neutral [3+2]‐cyclization between 2 H ‐azirines and azodicarboxylates (Scheme 1; previous work) [15] .…”
Section: Introductionmentioning
confidence: 99%